Benign monomelic amyotrophy with proximal upper limb involvement: case report Amiotrofia monomélica benigna com comprometimento proximal do membro superior: relato de caso - Marco Antonio Orsini Neves; Marcos R.G. de Freitas; Mariana Pimentel de Mello; Carlos Henrique Dumard; Gabriel R. de Freitas; Osvaldo J.M. Nascimento (Arquivos de Neuro-Psiquiatria)
Monomelic amyotrophy (MA) is a rare condition in which neurogenic amyotrophy is restricted to an upper or lower limb. Usually sporadic, it usually has an insidious onset with a mean evolution of 2 to 4 years following first clinical manifestations, which is, in turned, followed by stabilization. We report a case of 20-years-old man who presented slowly progressive amyotrophy associated with proximal paresis of the right upper limb, which was followed by clinical stabilization 4 years later. Eletroneuromyography revealed denervation along with myofasciculations in various muscle groups of the right upper limb. We call atention to this rare location of MA, as well as describe some theories concerning its pathophysiology . A amiotrofia monomélica é condição rara em que a amiotrofia neurogênica é restrita somente a um membro superior ou inferior. Usualmente esporádica, possui um início insidioso e evolução lenta de 2-4 anos após as primeiras manifestações, seguida por estabilização. Relatamos o caso de um homem que aos 20 anos apresentou lentamente amiotrofia e paresia proximal no membro superior direito, estabilizando-se em quatro anos. A eletroneuromiografia identificou a presença de desnervação e fasciculações em diversos músculos proximais do membro superior direito. Chamamos a atenção para esta rara localização desta entidade, assim como descrevemos algumas das hipóteses da fisiopatologia.